Analisa ANALISA STRUKTUR MIKRO, KANDUNGAN LIGNIN DAN HEMISELULOSA SERAT PELEPAH SAWIT AKIBAT PERLAKUAN ALKALI - Hendriwan Fahmi; syaiful malik jenifer; anrinal anrinal (Retii, 2020)
The use of natural fibers from palm frond fibers in the manufacture of composite materials has its advantages, including high specific strength and modulus, low price, low density, lower population emissions, and is common or recyclable. The production of the material starts from the natural decomposition of the palm frond fibers. After the palm fronds have rotted, the process of extracting fibers is carried out using a cloth brush or beating them against the board so that the dirt is removed so that it gets the best fiber. Furthermore, the fibers were soaked in 5% NaOH solution for 1,2,3,4 hours and without NaOH treatment, after that, they were dried using an oven at 105 ° C. Tests carried out the lignin and hemicellulose content and the microstructure of the palm frond fibers with the effect of 5% NaOH treatment and without treatment. From the test results, it was found that the lowest lignin content was in 5% NaOH treatment for 4 hours 22.1030%, and the highest lignin content was in 5% NaOH treatment for 1 hour 29, 8694%, and the highest hemicellulose was found without NaOH treatment, namely 26.6343% and the lowest was the need for NaOH for 1 hour 22,1164%. As well as the results of research on the microstructure of palm frond fibers without treatment and with 5% NaOH treatment for 1,2,3, and 4 hours, there were cavities in the fibers. The longer the treatment, the cavities become more open